Level Crossing Rate of Macro-diversity System with Two Micro-diversity SC Receivers over Correlated Gamma Shadowed α–µ Multipath Fading Channels. Issue 2 (3rd March 2016) - Djosic, Danijel B.; Stefanovic, Dusan M.; Stefanovic, Caslav M.
ABSTRACT: In this article, macro-diversity structure with macro-diversity selection combining (SC) receiver and two micro-diversity SC receivers operating over correlated shadowed multipath fading channel are analysed. Received signal is subjected simultaneously to α –µ short-term fading and gamma long-term fading (shadowing) resulting in system performance degradation. Macro-diversity SC receiver aims to reduce gamma shadowing effect while micro-diversity SC receivers aim to mitigate α – μ small-scale multipath fading effects. Useful infinite series expressions for the second-order statistical measure such as level crossing rate (LCR) of macro-diversity SC receiver output signal is efficiently derived. Numerical results are presented to examine the influence of various gamma shadowing and α– µ multipath fading parameters on LCR of the proposed system.